El programa del manejo integrado de vectores en el marco de la pandemia por COVID-19 en Medellín, Colombia. - Rojo-Ospina, Raúl A.; Quimbayo-Forero, Marcela; Calle-Tobón, Arley; Bedoya-Patiño, Sindy C.; Gómez, Maribel; Ramírez, Astrid; Sánchez, Johnny; Silva-Alzate, Juan F.; Montes-Zuluaga, Carlos J.; Cadavid, Jorge M.; Henao-Correa, Enrique A. (Biomédica: Revista del Instituto Nacional de Salud, 2023)
Introduction: The COVID-19 pandemic pressured health care systems to remain alert and active in their vector-borne disease control and prevention programs, leading to changes in vector control strategies in urban areas affected by dengue, Zika and chikungunya. Objective: To describe the adaptations made to the vector control and surveillance program in Medellín during the COVID-19 health emergency. Materials and methods: Once the health emergency started, biosecurity protocols were developed. Entomological surveillance was strengthened from the institutional environment instead of homes. Data was collected in Medellín from 2018 to 2021 during the vector control and surveillance program activities, which included epidemiological and entomo- virological surveillance, entomological index survey, ovitrap monitoring, community mobilization, search and elimination of mosquito breading sites, and chemical control. These actions were adapted and/or increased to promote self-care among communities in total and partial confinement, and to develop prevention and control measures. Results: Mosquito monitoring was increased by 40% using ovitraps, entomological- virological surveillance showed an increase in 2020 of 34,4% compared to 2019 and virtual media was used to keep and improve contact with the community. Conclusion: The COVID-19 pandemic had a significant impact on arbovirus prevention and control programs. The city of Medellín quickly adapted its entomo-virological surveillance activities, control measures, and the contact with the community during the pandemic, which allow the Integrated Vector Management program to remain active in the city.